Temporal dynamics of SARS-CoV-2 phylogenetic diversity in Central Brazil reveals evolutionary shifts among variants of concern during the pandemic - Diniz-Filho, José Alexandre Felizola; Nunes, Rhewter; Targueta, Cintia Pelegrineti; dos Santos Braga Ferreira, Ramilla; Melo-Ximenes, Amanda; de Oliveira Dias, Renata; de Curcio, Juliana Santana; Melo e Silva, Daniela; Dias e Souza, Menira Borges de L.; Fiaccadori, Fabíola Souza; de Paula Silveira Lacerda, Elisângela; Toscano, Cristiana Maria; et al. (Frontiers in Microbiology, 2025)
The COVID-19 pandemic has led to substantial health, economic, and social impacts worldwide, and now, after more than 5 years since the start of the pandemic, it is possible to retrospectively evaluate patterns of SARS-CoV-2 spread and its consequences. Here we investigate the temporal dynamics of SARS-CoV-2 phylogenetic diversity in Goiás State, Central Brazil, using genomic data from 8,937 viral sequences obtained from GISAID between March 2020 and October 2024. Phylogenetic diversity was assessed through median pairwise distances (MedPD) and phylogenetic eigenvector regression (PVR) derived from principal coordinate analysis (PCoA) of pairwise distances among sequences. Results show evolutionary shifts associated with the emergence of new variants of concern (VOCs), particularly Gamma and Omicron, corresponding to distinct peaks in phylogenetic diversity through time. The initial rise in MedPD coincided with the Gamma variant’s emergence in early 2021, while a more pronounced peak followed the spread of the Omicron variant in late 2021. Although a third peak appeared in late 2023, it was based on smaller sample sizes and did not correspond to a major VOC. Moreover, the temporal dynamics of MedPD tends to mirror the epidemiological characterization of the epidemic over time, including morbidity and mortality, reflecting the impact of vaccination in the disease burden of subsequent variants. The strong phylogenetic signal over time, reflected in the first PCoA axis, highlights the evolutionary trajectory of the virus. This study illustrates how genomic surveillance provides critical insights into viral diversification and public health responses during pandemics.